-2x+3+5x=9/7

Simple and best practice solution for -2x+3+5x=9/7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2x+3+5x=9/7 equation:



-2x+3+5x=9/7
We move all terms to the left:
-2x+3+5x-(9/7)=0
We add all the numbers together, and all the variables
-2x+5x+3-(+9/7)=0
We add all the numbers together, and all the variables
3x+3-(+9/7)=0
We get rid of parentheses
3x+3-9/7=0
We multiply all the terms by the denominator
3x*7-9+3*7=0
We add all the numbers together, and all the variables
3x*7+12=0
Wy multiply elements
21x+12=0
We move all terms containing x to the left, all other terms to the right
21x=-12
x=-12/21
x=-4/7

See similar equations:

| 3(n-4)-8=0.5n | | 22.00+24.50z=47.00+18.25z | | 7/4d+4/3=-1/3 | | -3.6a=4a | | x+7.50=2(x+7.50) | | 8s–1=6s–5 | | -8+12-17=x | | s−83=-59 | | x-1/2-2x=5/2 | | 4r-r=-15 | | (x+4)+2(x+2)=2x+12 | | 4c=10=2(2c-5) | | h+91=-5 | | x=8=19 | | F(x)=0x | | x+77.2+100.6=141.4 | | x/2-12=5 | | X+122=x+80 | | -4.9x^2+29.4x+2.5=0 | | 2.73+0.06x=13.48-0.14x | | -212=-4x-4(6x-10) | | F(x)=2x+11x=5 | | -4.9x^2+29.4+2.5=0 | | 0.75x=18-0.5x | | f−-22=24 | | 12.73+0.06x=13.48-0.14 | | 8(3m+15)=2(m-2) | | 20y2+21y+4=0 | | 5y^2+20y-35=0 | | 2/7x-3+2x=-69/7 | | d+-1=-46 | | |4-4v|=28 |

Equations solver categories